UTILIZATION OF AMARANTHUS SPP. GRAINS IN FOOD - Bodroža Solarov, Marija; Šimurina, Olivera; Kojić, Jovana; Krulj, Jelena; Filipović, Jelena; Cvetković, Biljana; Ilić, Nebojša (Food and Feed Research, 2022)
Recently there has been a rediscovery of some ancient crops due to increased consumer demands for healthier diet with medicinal and therapeutic effects. One such crop is a pseudocereal Amaranthus sp. which is nutritionally more favourable than many common  cereals and meets most of the requirements of modern diets. Incorporation of amaranth species in food formulations would expand the assortment of food products on market. High nutritional quality and potential functionality of amaranth food products has been a subject of extensive scientific research. This study aims at reviewing the currently available data on application of amaranth grains in food industry and manufacture and focuses on the functionalities of these products, providing an overview of the current amaranth value chain.
Keywords: bakery; pasta; snacks; edible films; malted food; amaranth